Reading Theories and Reading Comprehension; Review and Discussed - Herri Susanto (Universitas Dian Nuswantoro, 2019)
Abstract. In this article, several reading theories need to be reviewed in their relationships to read understanding educators and English lecturers. Three other Reading Models, Bottom-Up, Top-Down, and Interactive, are discussed in the Schema Theory at the theoretical stage. The history of reading training, kinds and purposes of reading, and cognitive reading abilities will be discussed in checking the reading understanding. Finally, it reviews six variables that are engaged in understanding English texts.Keywords: comprehension, models of reading, schema theoryAbstrak. Dalam artikel ini, beberapa teori bacaan perlu ditinjau dalam hubungannya untuk membaca pemahaman para pendidik dan dosen bahasa Inggris. Tiga Model Membaca diantaranyamodel Bottom-Up, Top-Down, dan Interactive dibahas dalam Schema Theory pada tahap teoretis. Rentetan uji coba, jenis dan tujuan membaca, serta kemampuan membaca kognitif dibahas dalam memastikan pemahaman membaca. Akhirnya, terdapat review terhadap enam variabel yang terlibat dalam memahami teks bahasa Inggris.Kata kunci: membaca, model membaca, teori schema